PENINGKATAN KINERJA GURU MELALUI WORK OF LIFE, KNOWLEDGE MANAGEMENT DAN ETOS KERJA DI SMK SWASTA GUGUS 2 KOTA TANGERANG SELATAN - Jonathan Yordania Pratna; Siti Zubaidah; Herdi Wisman Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze efforts to improve teacher performance through Work of Life, Knowledge Management, and Work Ethic at Private Vocational High Schools Cluster 2, South Tangerang City. The study employed a quantitative approach using a survey method. The research sample consisted of 145 teachers, selected using the Slovin formula. Data were collected through questionnaires and analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that Work of Life, Knowledge Management, and Work Ethic have both partial and simultaneous positive and significant effects on Teacher Performance. Partially, Work of Life has a standardized regression coefficient (Beta) of 0.433 (t = 8.314; Sig. = 0.000), Knowledge Management has a Beta coefficient of 0.315 (t = 5.981; Sig. = 0.000), and Work Ethic has a Beta coefficient of 0.258 (t = 4.945; Sig. = 0.000). Simultaneously, the ANOVA test shows that the calculated F-value (F = 391.664) is greater than the critical F-value (F = 2.695) with a significance level of 0.000 < 0.05, indicating that the three independent variables jointly have a positive and significant effect on Teacher Performance. The coefficient of determination (R² = 0.906) indicates that 90.6% of the variation in Teacher Performance can be explained by Work of Life, Knowledge Management, and Work Ethic, while the remaining 9.4% is influenced by other factors outside the research model. Based on the standardized regression coefficients (Beta), Work of Life is the most dominant variable affecting Teacher Performance, followed by Knowledge Management and Work Ethic. The findings suggest that improving teacher performance requires strengthening Work of Life practices, optimizing Knowledge Management, and continuously developing Work Ethic to enhance teachers' professionalism and support the achievement of higher educational quality in Private Vocational High Schools Cluster 2, South Tangerang City.